PENERAPAN MODEL TEAMS GAMES TOURNAMENT BERBANTUAN MEDIA WORDWALL TERHADAP KEAKTIFAN BELAJAR SISWA - Septiana, Elisa; Fakhriyah, Fina; Agung Santoso, Denni (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2025)
This research is based on the low level of learning activity of fourth grade students at SD 4 Gulang. This study aims to describe the effect of the Teams Games Tournament (TGT) model assisted by wordwall on student learning activity. The research applied is a research with a quantitative pre-experiment approach. The subjects of this study included all fourth grade students at SD 4 Gulang as a population and a sample of 21 students. The results of the study indicate that there is a positive influence of the application of the teams games tournament model assisted by wordwall on student learning activity with the results of the Paired Sample T-test sig. 0.000 <0.05, it can be concluded that there is a significant influence of the application of the teams games tournament model assisted by wordwall which makes students actively involved during learning. In addition, based on the results of the descriptive statistical test, it can be seen that there is an increase in learning activity during learning. The results of the N-Gain test show an increase in student activity at each meeting, namely at meeting 1 with an average of 46.93 students then increasing at meeting 2 by 69.38. In the third meeting, the average student activity increased to 87.92, which means that each meeting saw a significant increase in student learning activity. In conclusion, the implementation of the Teams Games Tournament model with the help of word walls was quite effective in increasing the learning activity of fourth-grade students at SD 4 Gulang.